1999
DOI: 10.1046/j.1524-475x.1999.00362.x
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin enhances wound healing in streptozotocin induced diabetic rats and genetically diabetic mice

Abstract: Tissue repair and wound healing are complex processes that involve inflammation, granulation and tissue remodeling. Interactions of different cells, extracellular matrix proteins and their receptors are involved in wound healing, and are mediated by cytokines and growth factors. Previous studies from our laboratory have shown that curcumin (diferuloylmethane), a natural product obtained from the rhizomes of Curcuma longa, enhanced cutaneous wound healing in rats and guinea pigs. In this study, we have evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
188
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 296 publications
(210 citation statements)
references
References 33 publications
11
188
0
1
Order By: Relevance
“…Moreover, proliferation of fibrous connective tissue was observed notably in wounds of turmeric group at day 3 (D3). This result upholds the finding of Sidhu et al (1999). It may be due to the anti-inflammatory ability of marigold flower (Hamburger et al, 2003) and turmeric (Aggarwal et al, 2003) respectively.…”
Section: Resultssupporting
confidence: 85%
“…Moreover, proliferation of fibrous connective tissue was observed notably in wounds of turmeric group at day 3 (D3). This result upholds the finding of Sidhu et al (1999). It may be due to the anti-inflammatory ability of marigold flower (Hamburger et al, 2003) and turmeric (Aggarwal et al, 2003) respectively.…”
Section: Resultssupporting
confidence: 85%
“…A therapeutic agent selected for the treatment of wounds should ideally improve one or more phases of healing without producing deleterious side effects. Curcumin, an important active principle of turmeric (Curcuma longa), has been proved to promote wound healing in various wound models (Sidhu et al, 1998(Sidhu et al, , 1999. In this study, the per cent contraction of wound was significantly higher in treated animals which are in agreement with other previous workers.…”
Section: Effect Of Curcumin On Endothelial Cell Marker Protein Cd-31 supporting
confidence: 92%
“…5) wounds favours more collagen synthesis, well formed granulation tissue and blood vessels in the treated samples. Sidhu et al, 1999, had also reported that the curcumin treatment led to an increased formation of granulation tissue including greater cellular content, neovascularization and a faster reepithelialization of wound in both diabetic as well as hydrocortisone impaired wounds by regulating the expression of TGF-β1, its receptors and nitric oxide synthase during wound healing .…”
Section: Effect Of Curcumin On Endothelial Cell Marker Protein Cd-31 mentioning
confidence: 96%
See 1 more Smart Citation
“…These processes aim to ensure the regeneration www.intechopen.com and reconstruction of anatomical and functional disturbances of the skin [Chattopadhyay et al, 2002]. The repair of damaged tissues occurs as a sequence of events that included inflammation, proliferation and migration of different cell types [Sidhu et al, 1999]. At the dose of 0.44 mg used only once the essential oil healed wounds for 96h.…”
Section: Discussionmentioning
confidence: 99%